Peranan Ulama Silam Memperkenalkan Pemikiran Maqāṣid Al-Sharī‘Ah Dalam Kemahiran Berfikir Aras Tinggi: Satu Analisis: The Role of Early Islamic Scholars in Introducing the Philosophy of Maqāṣid al-Sharī‘ah in the Higher Order Thinking Skills: An Analysis - Ahmad, Ridzwan; Mokhtar, Mohd Nizam; Wahab, Raihana Abdul (Jurnal Fiqh, 2020)
The Higher Order Thinking Skills (HOTS) is one of the forms of thinking skills that had been practiced by the early Islamic scholars such as Imām alHaramayn Abu Ma‘alī al-Juwaynī, Imam al-Ghazālī, Imām Fakhr al-Dīn al-Razī, and also, in maqāṣid al- sharī‘ah. Yet, HOTS is often associated with Western scholars, and has never been associated with the elements of maqāṣid al-sharī‘ah. This study aims to prove that Islamic scholars had been practicing HOTS but Western scholars introduced a new term to it and through systematic studies proved their ideas to be acceptable. It was claimed that the idea was the result of Western thoughts and studies. Among the leading scholars who pioneered thinking skills were al-Qabisī (died in 420H) who introduced the neuklitic model or model of concentration and communication, Imam al-Ghazālī (died in 505H) who introduced the Progressive Order model, Ibn Khaldūn (died in 808H) who introduced the Malakat model, and others. In the Malaysian context, the concept of maqāṣid al-sharī‘ah has been applied in the teaching and learning process in the informal education of the pondok system that has been in existence before the country gained independence. Due to the decline in performance among Malaysian school students, the Ministry of Education introduced the Critical and Creative Thinking Skills and HOTS which eventually led to the transformation of the education curriculum known as the Malaysian Education Development Plan (PPPM 2013 -2025). The results of the study show that HOTS had originated from the skills of early Muslim scholars who used the maqāṣid alsharī‘ah approach rather than solely being the ideas of the Western scholars. Through this approach, a local wisdom is created that ultimately produces high school students in Malaysia who are capable of thinking in a more matured fashion in dealing with issues in their lives. It is hoped that the splendid skills of thinking will be restored using the theory and method of maqāṣid al-sharī‘ah which had been advocated among Muslims and had successfully produced many great scholars.